2020
DOI: 10.17576/gema-2020-2002-09
|View full text |Cite
|
Sign up to set email alerts
|

Parasites, Herbivores and Dried Fish: Dehumanising Metaphorical Blends in Japanese

Abstract: In the context of a vast body of research on the role and function of conceptual metaphor in linguistic representation of non-dominant or non-normative social groups, the present paper deals with metaphorical blending found in a number of expressions used to describe deliberately single people forming part of the Japanese society. Expressions such as parasaito shinguru ("parasite singles"), sōshoku-kei danshi ("herbivorous men"), and himono onna ("dried-fish women") are used as labels designating particular gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…To some degree, the findings also corroborate previous research findings on the dehumanizing metaphors (e.g., Barasa & Opande, 2017;Musolff, 2015;O'Brien, 2009;Prażmo, & Augustyn, 2020;Usman, 2017). All the abstract concepts used to describe the concretely perceivable concepts in metaphors are usually are close to the people's existence and surroundings.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…To some degree, the findings also corroborate previous research findings on the dehumanizing metaphors (e.g., Barasa & Opande, 2017;Musolff, 2015;O'Brien, 2009;Prażmo, & Augustyn, 2020;Usman, 2017). All the abstract concepts used to describe the concretely perceivable concepts in metaphors are usually are close to the people's existence and surroundings.…”
Section: Discussionsupporting
confidence: 88%
“…On the contrary, in the Kenyan context, Barasa and Opande (2017) found that people used animals as the concepts to describe women in Bukusu and Gusii proverbs. A similar thing also happened in Japan context (Prażmo, & Augustyn, 2020), where people who do not conform to conventional societal roles are labeled with animals.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Indeed, our results are consistent with some scholars who speculated on the relationship between the behavioral immune system theory and dehumanization. For example, Prażmo and Augustyn ( 2020 ) stated that the metaphorical notion of a social and bio parasite to describe immigrants is strongly related to the activation of the behavioral immune system, whose aim is to protect us from having any other close contact with potentially contaminated. According to the authors, it may also affect our reasoning and decision‐making in relation to political inclinations and attitudes toward others.…”
Section: Discussionmentioning
confidence: 99%
“…This derogatory and stigmatising power of language has been extensively studied by, among others, metaphor scholars. Conceptual metaphor in general, and dehumanising metaphors in particular serve the purpose of denigrating and ostracising certain groups of people or individuals (Musolff, 2007(Musolff, , 2015Prażmo & Augustyn, 2020). Linguists are thus, indubitably, well aware of the potential deleterious effect that naming of the virus in an ethnically-loaded way may create.…”
Section: Statement Of the Problemmentioning
confidence: 99%